PENGARUH PEMBINAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS DIKPORA KABUPATEN TOJO UNA-UNA - Bindiab, Ramla H. (Katalogis, 2017)
The study aims to analyze simultaneous and partial influence coaching and work environment on officers’ performance in The Department of Education, Youth, and Sport Tojo Una-Una. Respondents consist of 41 officers in The Department of Education, Youth, and Sport Tojo Una-Una. Tool of analysis is multiple linear regressions. The results indicate that both simultaneously and partially, coaching and work environment have insignificant influence on officers’ performance in The Department of Education, Youth, and Sport Tojo Una-Una.